Cognitive Behavioral Therapy (CBT) Approach In Adolescents With Online Game Addiction - Aulia, Krisma; Utami, Margaretha Sih Setija (Eduvest - Journal of Universal Studies, 2025)
Online games are popular entertainment in all circles, especially among teenagers. Game addiction is excessive and repetitive gaming activities that can result in impulse disorders, anxiety, social problems, and the inability to control gaming activities. Online game addiction needs to be overcome, one of which is by providing Cognitive Behavioral Therapy (CBT). Cognitive Behavioral Therapy is a psychotherapy that integrates two approaches: cognitive therapy and behavioral therapy. This study aims to find out the role of Cognitive Behavioral Therapy as the right choice to help adolescents who are addicted to online games. The research method used is in the form of a literature review. Researchers analyzed some previous research journals related to Cognitive Behavioral Therapy and online game addiction. The results of the study show that Cognitive Behavioral Therapy is an effective method to reduce online game addiction in adolescents. Cognitive Behavioral Therapy can help adolescents learn to restrain and control excessive cravings to play games so that they can reduce impulsivity disorders, anxiety, and social problems. Adolescents who are addicted to online games can benefit from the help of counselors in identifying, understanding, and changing unhealthy mindsets and behaviors so that they can improve their quality of life by doing more beneficial positive activities.